The added value of social capital in Poland in light of the experimental data - Markowska-Przybyła, Urszula (Renta kapitału społecznego w Polsce w świetle danych eksperymentalnych, 2019)
The article presents the issues of social capital, the benefits it can bring and the concept of added value that it can create for companies located in a favorable environment. The purpose of the article is to indicate which regions of Poland and categories of places, due to their size, are more abundant than others in social capital resources and may bring enterprises an extraordinary added value - a social capital added value. The research was based on the results of unique research on social capital - based on the observation of behavior. The research method was the method of experimental economics, the study was conducted on a sample of 1540 people in all regions of Poland in 2014. The second part of the work presents the issues of social capital, its significance and the added value it yields. The third part presents the research method. The fourth one - the essential part of the work - presents the results of the research on the level of the social capital of regions and various classes of towns. The fifth part points to the empirical evidence of the relationship between Poland’s social capital (measured on the basis of conducted research) and the economic achievements. The last part is a summary
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 64-78
Keywords: social capital; added value; regions; Poland; experimental economy; kapitał społeczny; renta; regiony; Polska; ekonomia eksperymentalna